Influência da temperatura no crescimento micelial de linhagens de Lentinula edodes - Athayde, Marina Bortoleto [UNESP]; Zied, Diego Cunha [UNESP]; Minhoni, Marli Teixeira de Almeida [UNESP]; Andrade, Meire Cristina Nogueira de [UNESP] (My University, 2010)
The objective of the present work was to evaluate the in vitro mycelial growth of ten L. edodes strains (LED 12, LED 20, LED 25, LED 27, LED 33, LED 35, LED 51, LED 55, LED 58 and LED 75) submitted to the temperatures of 15, 20 and 25 ºC. An agar medium prepared with eucalyptus wood extract and soy bran was used and radial measurement of the mycelial growth of L. edodes strains was performed. The experimental design was totally randomized, in a 10 x 3 factorial scheme. Each treatment corresponded to a Petri plate and consisted of 5 repetitions. It was verified that L. edodes growth is influenced by the incubation temperature, that is the temperature of 25 ºC was the most favorable for the mycelial growth of all L. edodes strains, especially for LE 75, LE 55, LE 33 and LE 12 strains, which obtained the highest mycelial growth averages at 25 ºC at the end of the cultivation cycle.

O objetivo do trabalho foi avaliar o crescimento micelial in vitro de dez linhagens de L. edodes (LED 12, LED 20, LED 25, LED 27, LED 33, LED 35, LED 51, LED 55, LED 58, e LED 75), quando submetidas às temperaturas de 15, 20 e 25 ºC. Utilizou-se um meio agarizado preparado com extrato de madeira de eucalipto e farelo de soja, no qual fez-se a medição radial do crescimento micelial das linhagens de L. edodes. O delineamento experimental foi inteiramente casualizado, em esquema fatorial 10 x 3, cada tratamento constando de 5 repetições, correspondente a uma placa de Petri. Verificou-se que o crescimento de L. edodes é influenciado pela temperatura de incubação, sendo que a temperatura de 25 °C foi mais favorável para o crescimento micelial de todas as linhagens de L. edodes. Destaque foi dado às linhagens LE 75, LE 55, LE 33 e LE 12 que obtiveram as maiores médias de crescimento micelial a 25 °C ao final do ciclo de cultivo.
Temperature influence on the mycelial growth of Lentinula edodes strains
Keywords: Fungi; Mycelium; Mushroom; Fungos; Micélio; Cogumelo